PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI METODE SNOWBALL THROWING PADA SISWA KELAS V SDN 3 SOCO - Inayyah Nawang Wulan; Al-Amin (CV. ADIBA AISHA AMIRA, 2026)
This study was motivated by the poor learning outcomes in Pancasila Education among fifth-grade students at SD Negeri 3 Soco, Slogohimo Subdistrict, Wonogiri Regency. The learning process, which still tends to be teacher-centered, causes students to be less active, easily bored, and less engaged in learning activities. This situation has resulted in low student academic achievement, as evidenced by low test scores and a low percentage of students meeting learning standards. This study aims to improve learning outcomes in Pancasila Education through the application of the Snowball Throwing method. This study is a Classroom Action Research (CAR) conducted in two cycles. Each cycle includes the planning, implementation, observation, and reflection stages. The research subjects were 10 fifth-grade students at SD Negeri 3 Soco, consisting of 5 male and 5 female students. Data collection techniques included observation, interviews, documentation, and learning outcome tests. The data were analyzed using qualitative descriptive techniques. The results of the study indicate that the application of the Snowball Throwing method can improve student learning outcomes. In the pre-cycle phase, the class average score was 61.1 with a learning achievement rate of 20%. After the intervention in Cycle I, the average score increased to 76.3 with a learning achievement rate of 70%. A further improvement occurred in Cycle II, with the average score reaching 90.0 and the learning achievement rate at 100%. In addition to improving learning outcomes, the Snowball Throwing method can also increase student engagement, participation, and confidence in asking questions, answering questions, and expressing opinions during the learning process. Thus, the Snowball Throwing method is considered effective for improving Pancasila Education learning outcomes among fifth-grade students at SD Negeri 3 Soco, Slogohimo Subdistrict, Wonogiri Regency.